PENGARUH PERTUMBUHAN MODAL SENDIRI DAN LABA TERHADAP RASIO RISK BASED CAPITAL DI PT ASURANSI TAKAFUL KELUARGA INDONESIA - Irawati Irawati (Istinbath | Jurnal Penelitian Hukum Islam, 2017)
This study based on the performance of PT. Asuransi Takaful Keluarga Indonesia, to measure the performance of the company can be obtained from the financial information contained in the financial statements, in those statements contained ratios one of them is the ratio Risk based capital. The factors that are thought to affect the Risk based capital ratio is the own capital growth and profit growth. The company must increase its own capital and profit growth, but the increase in equity and profit are not always able to increase the Risk based capital ratio. The purpose of this study was to determine how much influence the growth of their own capital as variable X₁ and profit as variable X₂ on the Risk based capital ratio (Y) partially and simultaneously. Framework in this study is the Growth of own capital, Growth of profit and Risk based capital ratios. The insurance companies try to increase their own capital but carelessness in the capital increase it self can increase the volume of claims and erode existing capital so as to reduce the Risk based capital ratio. Another factor is profit growth, profit growth is a reflection of the success of a company, but earnings growth does not guarantee could increase its Risk based capital because usually the company also increased its operations so as to reduce the Risk based capital. This research method is quantitative method with the source data is secondary data obtained from official web Takaful Keluarga (www.takaful.co.id), the official web of Otoritas Jasa Keuangan (www.ojk.go.id), Bapepam official website (www.bapepam.go.id) and the terms of its goal, this study includes research into explanatory (explanatory research). Based on the results of research conducted by partial, own capital growth did not significantly affect the Risk based capital ratio , because the value of t test (-0.642) < t table (2.306), the relationship profit growth against a Risk based capital ratio partially also not significant effect because the results t calculate the profit growth in the Risk based capital ratio is -2.714, then t ( -2.714 ) < t table ( 2.306 ) and the simultaneous growth equity capital, profit return on Risk based capital ratio does not significantly effect because it is based on the analysis of F count ( 3.285 ) < 4:459 (F-tabel)